Synthesis and future research directions linking tree diversity to growth, survival, and damage in a global network of tree diversity experiments - Grossman, Jake J.; Vanhellemont, Margot; Barsoum, Nadia; Bauhus, Jürgen; Bruelheide, Helge; Castagneyrol, Bastien; Cavender-Bares, Jeannine; Eisenhauer, Nico; Ferlian, Olga; Gravel, Dominique; Hector, Andy; Jactel, Hervé; et al. (Environmental and experimental botany, 2018)
•TreeDivNet is a global network of 25 tree biodiversity experiments.•A review of 158 publications reveals diversity affects tree growth, survival, and damage.•Research addresses mechanisms of biodiversity-ecosystem functioning relationships.•Tree diversity experiments expand upon past grassland diversity research. Despite considerable research demonstrating that biodiversity increases productivity in forests and regulates herbivory and pathogen damage, there remain gaps in our understanding of the shape, magnitude, and generality of these biodiversity-ecosystem functioning (BEF) relationships. Here, we review findings from TreeDivNet, a global network of 25 tree diversity experiments, on relationships between levels of biodiversity and (a) tree growth and survival and (b) damage to trees from pests and pathogens. Tree diversity often improved the survival and above- and belowground growth of young trees. The mechanistic bases of the diversity effects on tree growth and survival include both selection effects (i.e., an increasing impact of particular species in more species-rich communities) and complementary effects (e.g. related to resource differentiation and facilitation). Plant traits and abiotic stressors may mediate these relationships. Studies of the responses of invertebrate and vertebrate herbivory and pathogen damage have demonstrated that trees in more diverse experimental plots may experience more, less, or similar damage compared to conspecific trees in less diverse plots. Documented mechanisms producing these patterns include changes in concentration, frequency, and apparency of hosts; herbivore and pathogen diet breadth; the spatial scale of interactions; and herbivore and pathogen regulation by natural enemies. Our review of findings from TreeDivNet indicates that tree diversity experiments are extending BEF research across systems and scales, complementing previous BEF work in grasslands by providing opportunities to use remote sensing and spectral approaches to study BEF dynamics, integrate belowground and aboveground approaches, and trace the consequences of tree physiology for ecosystem functioning. This extension of BEF research into tree-dominated systems is improving ecologists’ capacity to understand the mechanistic bases behind BEF relationships. Tree diversity experiments also present opportunities for novel research. Since experimental tree diversity plantations enable measurements at tree, neighbourhood and plot level, they allow for explicit consideration of temporal and spatial scales in BEF dynamics. Presently, most TreeDivNet experiments have run for less than ten years. Given the longevity of trees, exciting results on BEF relationships are expected in the future.